International travel agency and tour operation management - Dhiman, Mohinder Chand, 1967-; Chauhan, Vinay (Business Science Reference, 2019)
"This book examines all aspects of travel agency and tour operation management as well as the latest methodologies, tools, and theories regarding tourism development and sustainability"--